Simulated versus physical bench tests: The economic evaluation of the InSilc platform for designing, developing, and assessing vascular scaffolds. Issue 25 (25th June 2021) - Mincarone, Pierpaolo; Bodini, Antonella; Sabina, Saverio; Colella, Riccardo; Tumolo, Maria Rosaria; Fawdry, Martin; Fotiadis, Dimitrios I.; Leo, Carlo Giacomo
Abstract: Background: In silico medicine allows for pre-clinical and clinical simulated assessment of medical technologies and the building of patient-specific models to support medical decisions and forecast personal health status. While there is increasing trust in the potential central role of in silico medicine, there is a need to recognize its degree of reliability and evaluate its economic impact. An in silico platform has been developed within a Horizon 2020-funded project (In-Silc) for simulations functional to designing, developing, and assessing drug-eluting bioresorbable vascular scaffolds. The main purpose of this study was to compare the costs of 2 alternative strategies: the adoption of In-Silc platform versus the performance of only physical bench tests. Methods: A case study was provided by a medical device company. The values of the model parameters were principally set by the project partners, with use of interviews and semi-structured questionnaires, and, when not available, through literature searches or derived by statistical techniques. An economic model was built to represent the 2 scenarios. Results: The InSilc strategy is superior to the adoption of physical bench tests only. Ceteris paribus, the costs are 424, 355[Euro sign] for the former versus 857, 811[Euro sign] for the latter. Conclusions: In silico medicine tools can decrease the cost of the research and development of medical devices such as bioresorbable vascular scaffolds. Further studies are needed to explore the impact of such solutions on the innovation capacity of companies and the consequent potential advantages for target patients and the healthcare system. Abstract : Supplemental Digital Content is available in the text